TRIPLE DEFICIT PRESSURE INDEX AND ESTIMATION OF THE FINANCIAL CRISIS: THE CASE OF TURKEY - Murat Akkaya (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The main indicators affecting short and longterm macroeconomic stability are budget deficits, current account deficit and savings deficits expressed as savings-investment imbalance. In the literature of Economics and Finance, there are many national and international studies on Twin Deficits Hypothesis. The triple deficit is also the balance of imbalance. The Triple Deficit Hypothesis is based on the relationship between the budget balance expressed as internal balance and the balance of savings and the current account balance representing the external balance. The main purpose of this study is to create a Triple Deficit Pressure Index for Turkey in 1998 - 2019 period. In addition, leading indicators that cause financial crises are investigated using the Triple Deficit Pressure Index. The study proves that Triple Deficit Pressure Index is valid in Turkey. In addition, there is one-way Granger causality for the Trıple Defıcıt Pressure Index.